Wide area tracking system based on LoRa devices - Holík, David; Arm, Jakub (Vysoké učení technické v Brně, Fakulta elektrotechniky a komunikačních technologií, 2024)
The work deals with wireless communication using LoRa (Long Range) technology categorized as LPWAN (Low Power Wide Area Network). The technoloy enables wireless data transmission over long distances more than 5 kilometers in urban or rural areas. The technology is used as the communication between ESP32-based devices providing their GPS data and time synchronization. The system also consists Raspberry Pi which provides the central LoRa station for near area. The communication between central and peripheral devices was established using open-source libraries. The central device might need to receive packets from surrounding devices concurrently, whichi is not possible using the designed device, thus a protocol needs to be established as discussed. Moreover, the communication with the public TTN network has been tested. Regarding the communication testing, test scenarios were designed.
Keywords: LoRa; LoRaWAN; IoT; LPWAN; GPS; Spreading Factor; The Things Network